Evaluating the Economic Impact of the 2016-2020 National Policy for Research, Develpoment, and Innovation in the Czech Republic - Salov, Filip (2025)
This thesis evaluates the economic impact of the National Research, Development, and Innovation Policy of the Czech Republic for the period 2016–2020. Employing two-way fixed effects difference-in-differences event-study and average treatment effect estimation on firm panel data, the study examines whether participation in publicly funded R&D programs, TRIO, ZÉTA, ÉTA, and THÉTA, affected the innovative output and economic performance of Czech firms and examines how the effect differed based on firm size and age. The findings suggest a limited and heterogeneous impact of policy. It incentivised employment growth, particularly among startups, and positively influenced innovation outputs, especially among SMEs and incumbent firms. However, no significant effect was observed on turnover and tangible fixed assets, suggesting weak commercialisation of new technologies and limited impact on firm production capacity.